Unmet needs as indicator of improving chronic care delivery system in China - Xia-Tong Ke (KeAi Communications Co., Ltd., 2021)
In 2009, China strengthened its public health service system. Since then, the country has made remarkable achievements in community-based chronic disease prevention and control; however, certain groups still have unmet needs. During 2019 to 2029, China will consolidate the top-level design of its medical health system. During this period, the coordination of department policies, improvement of service delivery mechanisms, building an integrated health service system, and other issues will be highlighted. This study will provide a basis for designing China's chronic disease prevention and control system during the next stage of development. We will consider the unmet needs of patients with chronic diseases as an indicator for remodeling the prediction system in combination with the elements and structural theories of complex health systems. In this article, we first introduce the definition and measurement methods of unmet needs. Second, we identify the existing unmet needs found among patients with chronic diseases with reference to the chronic disease prevention and control policies of China as well as current service items. Finally, we propose the design of community chronic disease service package for the next development stage based on unmet needs of patients with chronic diseases. We also provide suggestions for how to improve China's chronic care delivery system.